Phenomenological models of divine communication - Williams, Jack (2017)
This thesis undertakes an investigation into a specific form of religious experience, in which the subject reports to have received some articulable, linguistic communication from God. The investigation focuses on the thought of Jean-Luc Marion and Hans-Georg Gadamer in order to develop a phenomenological approach to understanding these divine communicative experiences. The thesis reaches three main conclusions: first, that"divine communication" is an important philosophical category, second, that any approach to understanding it must take into account hermeneutics, and third, that the concept of mediality might offer a way forward for understanding both divine communication and the life of faith.